A Review on Food Ordering System - Ratan, Himanshu; Rawat, Shubham Kumar; Kaur, Ravneet; Panwar, Sarthak; Swroop, Ishan (Journal of Advanced Research in Information Technology, Systems and Management, 2022)
In this technology-driven era, the Internet has evolved into one of the most powerful forms of media. As traditional media consumption declines and online media consumption increases, businesses need to change the way they work. The younger generation is one of the reasons for the increasing consumption of online media. Many large companies are beginning to adopt online business strategies to recover from the decline in sales. The method of online business is also implemented by restaurant companies. Currently, several new restaurant companies are offering bespoke (MTO) food products that do not have physical stores. Online platforms are used by such restaurants to contact customers. To increase sales, the Internet has brought the same benefits to traditional restaurants. The Internet has also led to the creation of "intermediaries" for the restaurant business, including: B. Grocery ordering and delivery company. These intermediaries partner with restaurants to list affiliated restaurants (that is, websites with mobile applications) on their online platforms. Customers can then order on the online platform. Revenues from these agents come from restaurant fees, customer delivery charges, or both. With the online food app, customers can create food delivery platforms, expand their choices and conveniences with a single tap on their mobile phone, and order from a variety of restaurants. How to cite this article: Ratan H, Rawat SK, Kaur R et al. A Review on Food Ordering System. J Adv Res Info Tech Sys Mgmt 2022; 6(1): 1-4.